Human platelets antigens influence the viral load of platelets after the interaction of the platelets with HCV and HIV in vitro - Tommasini Grotto, Rejane Maria [UNESP]; Cantao, Natalia Mirele [UNESP]; Padovani, Juliana Lara [UNESP]; Souza, Lenice do Rosario de [UNESP]; Silva, Giovanni Faria [UNESP]; Ferrasi, Adriana Camargo [UNESP]; Moura Campos Pardini, Maria Ines de [UNESP] (Soc Brasileira Medicina Tropical, 2016)
Introduction: In this study, we evaluated hepatitis C virus (HCV) and human immunodeficiency virus (HIV) - platelet interactions in vitro as well as human platelets antigen (HPA) polymorphisms. Methods: Platelets were obtained from 100 healthy HPA-genotyped volunteer donors and incubated with HIV or HCV. The viral load after in vitro exposure was detected. Results: The viral load in the platelets after exposure to the virus was higher in the HIV exposure than in the HCV exposure. Conclusions: HIV-platelet ligation could be more efficient than HCV-platelet interaction. Further, the HPA-1b allele seems to influence the interaction of platelets with HCV.
Keywords: Hepatitis C virus; Human platelets antigen polymorphisms; Human immunodeficiency virus